Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$a_{n-1} = ca_{n-2} $$


$$a_n = c \cdot c \cdot a_{n-2} $$
$$ = c \cdot c \cdot c \cdot a_{n-3} $$

$$ = c^na_0 $$

Why is there a iteration on the constant $c$ ?

share|cite|improve this question
Please work on formatting your questions with $\LaTeX$ as it makes them more readable. If you look at any formatting on the site and right click, Show Source will be what is inside dollar signs to make it. One set of dollar signs for inline, two for display. – Ross Millikan May 1 '11 at 2:18
It is not clear to me what your question is. You have shown the solution for $A_n$. This is almost the definition of exponentiation. – Ross Millikan May 1 '11 at 2:20
hi ross, I dont quite get why for every iteration constant C is added. example in $$a_{n-2} $$ there are 2 c. in $$a_{n-3} $$ there are 3 c – youcanlearnanything May 1 '11 at 2:23
This page might help you: – Nick Strehlke May 1 '11 at 2:35
up vote 2 down vote accepted

Your basic equation says that to get from $a_{n-2}$ to $a_{n-1}$ you multiply by $c$. If one step corresponds to multiplying by $c$, two steps should be multiplying by $c$ twice, which is $c\cdot c=c^2$ and $n$ steps should be multiplying by $c^n$.

An explicit example: take $a_0=1, c=2.$ Then your first equation says (taking $n=1$) $a_1=2a_0=2$, Then (taking $n=2$) $a_2=2a_1=4$ Does this help?

share|cite|improve this answer
$$a_{n-1} = ca_{n-2} $$ oh ok i got it. – youcanlearnanything May 1 '11 at 2:47

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.